Solanum baumii (Solanaceae), a New Species From Northeastern Thailand - Wannachai Chatan; Phukphon Munglue; Wilawan Promprom (The Scientific World Journal)
Solanum baumii Chatan and Promprom, a new species from Mukdahan Province, Phu Pha Yol National Park, northeastern Thailand, is morphologically described and illustrated. It is similar to Solanum barbisetum Nees and Solanum praetermissum Kerr ex Barnett, but it clearly differs from two latter species in several ways. Its young stems are armed with very few and thin prickles, which become unarmed as they age, with brownish-green prickles in live plants. The flowers are 4–5-merous, and the calyx tube is 5.0–5.5 mm long with brownish-green prickles, while the corolla is always white. The androecium consists of 4–5 stamens. The ovaries are glabrous except for sparsely glandular hairs near the apex, and the fruits are 1.0–1.2 cm in diameter, green at maturity. A key to these closely related species is presented. The preliminary conservation status was assessed, and the distinct morphological characters between the new and similar species were discussed.